Implementasi Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatan Hasil Belajar IPA Siswa Kelas VI SD Inpres Numba 2 - Samia M. Numba (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
Most of the science learning at SD Inpres Numba 2, especially in grade VI, still uses conventional methods. Lectures, assignments and exercises from teachers still dominate learning in class. Learning that involves activities is rarely done. Teachers are still central in informing facts and concepts through the lecture method. The purpose of this study was to determine the increase in science learning outcomes in grade VI SD Inpres Numba 2, Nangapenda District, Ende Regency. This type of research is classroom action research. The research subjects were 10 grade students consisting of 6 boys and 4 girls. Based on the results of the research implementation, the researcher concluded that the jigsaw cooperative model can improve student learning outcomes in science subjects in grade VI. This can be seen from the average value of cycle I and cycle II which increased from 61.5 to 67.5 in cycle I and 79 in cycle II.